VD_FINDINFO HC / 2015 / 1007 vom 13. November 2015 - VD Tribunal cantonal (2015)
ACTION EN DIVORCE, MESURE PROVISIONNELLE, MODIFICATION DES CIRCONSTANCES, CANADA, RETOUR | 176 al. 1 ch. 1 CC, 179 al. 1 CC, 276 al. 1 CPC (CH)